Stiffness Determination of Backfill-Rock Interface to Numerically Investigate Backfill Stress Distributions in Mine Stopes - Guangsheng Liu; Xiaocong Yang; Lijie Guo (Advances in Civil Engineering)
Numerical modeling is an effective and efficient method to investigate the stress distributions of backfill in stopes, which should be well understood in underground mining. Interface elements between backfill and rock in simulated stopes had been proved to be essential components, for which the stiffness parameters need to be assessed and assigned. However, few reports have revealed the effects of interface stiffness on backfill stress distributions, and there is not yet a clear solution to determine the interface stiffness to simulate stresses in backfilled stopes, except an empirical method for simply applying a high value suggested in FLAC manual. In this study, a new solution is first proposed to determine the normal stiffness and shear stiffness of interface elements, respectively, in numerical modeling of backfill stresses. The applicability of the solution has been verified by investigating backfill stress distributions in mine stopes of two widely used mining methods with variable stiffness values. The results show that the newly proposed method leads to totally the same backfill stress distributions with models applying the interface stiffness by the method in FLAC manual based on a “rule-of-thumb” but will save at least 20%–30% calculation time to improve modeling efficiency under the same simulation conditions and will carry much clear physical meanings corresponding to the interaction between backfill and rock walls in mine stopes. In addition, the vertical and horizontal stresses show good agreements with the analytical stresses predicted by the Marston equation under the at-rest state, which validates the reliability of the proposed solution for interface stiffness. Moreover, the plotting methods of stress distributions and the coefficient of lateral earth pressure of backfill in simulated stopes with proposed interface stiffness were discussed to further clarify the reasonable methods to investigate the backfill stresses in mine stopes, especially after considering the effects of the convergence from rock walls, which is a very significant and common phenomenon in practical mining engineering.